Change in Respiration, Chemical Composition and Leaf Area of Wheat Plants Infected with Flag Smut - DHARAMVEER; M. S. PANWAR (Seed Research, 2026)
Respiration rate of inoculated seeds of highly susceptible and susceptible varieties increased around 6 per cent as compared to control whereas in resistant varieties respiration increased by around one per cent. At tillering stage more than 25 and 14 per cent increase in respiration was recorded in highly susceptible and susceptible varieties respectively, whereas less than one per cent increase was noticed in resistant varieties. Leaf area reduced significantly (i.e. more than 55 and 45 per cent) in highly susceptible and susceptible varieties and no reduction was noticed in resistant varieties. Maximum in vitro dry matter digestibility (IVDMD) was recorded in straw obtained from totally diseased plants as compared to healthy control. Ether extract, crude protein and crude fiber decreased in diseased plants.